The Example of Hannah's Prayer Based on 1 Samuel 1:10-20 for Christian Women's Faith and Hope - Linda Joyce; Maria Titik Windarti (Green Philosophy: International Journal of Religious Education and Philosophy, 2024)
This article examines the example of Hannah's prayer based on the biblical text in 1 Samuel 1:10-20 and how her faith and hope can be an inspiration for Christian women in facing life's challenges. The study shows that through sincere prayer, faith, and hope, Hannah gained strength in overcoming severe personal struggles. Using a theological analysis approach, this article reveals the relevance of prayer as a form of devotion and trust in God, and identifies important principles drawn from Hannah's life to be applied in the lives of Christian women today.